First aid knowledge, attitude and awareness among nursing students: Relevance to nursing education - A’Aisyah Nur Farihah Binti Paharudin; Aini Ahmad; Annamma Kunjukunju; Puziah Yusof; Roziah Arabi; Syamilah Musa (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2022)
Background: First aid is a primary, initial, immediate and temporary care treatment to an injured person in a life-threatening situation to preserve life and minimise consequences of injuries until help from emergency medical services is obtained. Students who are expected to be working in the hospital settings should be exclusively trained regarding first aid skills that include choking, bleeding, fracture, shock, drowning, electrocution, spinal injuries, burns and scalds.Purpose: To identify the knowledge, practice, and awareness of first aid skills among first-year diploma nursing students in a private institution.Method: A quantitative cross-sectional study was conducted at one private Healthcare University College in Negeri Sembilan, Malaysia. The quantitative cross-sectional study was conducted using an adapted questionnaire. Later on, the acquired data was entered into Statistical Package for the Social Sciences(SPSS) version 25 for data analysis as adapted from the original article. Descriptive statistical tests were used to analyse data for demographic section, knowledge, attitude and awareness of first aid skills based on the items asked. Chi-square test was then used to analyse the relationship between level of knowledge and attitude regarding first aid among the respondents. There were 126 respondents obtained by using convenience sampling which consists of first-year diploma nursing students.Results: The result showed that majority of the respondents (67.5%) had only intermediate level of knowledge while majority of the respondents (81.7%) had good attitudes regarding first aid. The majority of the respondents (67.5%) had intermediate level of awareness regarding first aid.Conclusion: From this study, the value of Chi-Square (χ²) for this analysis was 0.600 with the significant level of 0.963 (p<0.05) showing there is no relationship between the level of knowledge regarding first aid and the level of attitude towards first aid. Thus meaning, the level of knowledge does not influence by attitude of respondents towards first aid.